PENGUNGKAPAN MANAJEMEN RISIKO TERHADAP NILAI PERUSAHAAN (Penelitian Empiris pada Perusahaan non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017) - Paramita Prasetiyani; Wahyu Meiranto (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of risk management disclosure toward the firm value of non financial sector firm that is listed in the Indonesia Stock Exchange (IDX) for the year of 2017. In addition, this study also examine whether with the existing of a more board disclosures by the firm would reduce the information asymmetry with the external information users that is needed for their decision making process. Based on signalling theory, which is about information asymmetry, if firms disclosed more informations, then they also should be having higher firm value. The population of this study are non financial sector firm that is listed in the Indonesia Stock Exchange (IDX) for the year of 2017. The sampling method is using pusposive sampling method resulting in total 285 firms selected from 482 population. The analytical tools in this research is using multiple regression analysis. The results show that disclosure of operational risk, strategic risk, and integrity risk information processing and technology risk have a significant and positive effect on the firm value while empowerment risk and integrity risk have no significant effect on the firm value.